The evaluation of the field performance of the neat and SBS modified hot mixture asphalt - Karakas, Ahmet Sertac; Kuloglu, Necati; Kok, Baha Vural; Yilmaz, Mehmet (Elsevier Sci Ltd, 2015)
The reason of using additives in Hot Mix Asphalt (HMA) is related to shortage of raw materials, demand for a longer service life of roads, a need for better physical and mechanical properties of asphalt pavement and thus a decrease in the maintenance and repair expenses. Additives such as polymer are mostly used for this purpose. In the present study, firstly the stiffness modulus, Marshall Stability, indirect tensile and fatigue resistance of the core samples collected at four different periods over a year from a road which is comprised of neat and styrene-butadiene-styrene (SBS) modified HMAs are examined. Secondly, how the qualities of the pavement are influenced by the temperature and environmental factors over a year was examined. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Hot Mix Asphalt; Stability; Modification; Temperature; Stiffness; Fatigue